2011
DOI: 10.1371/journal.pone.0023085
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Non-Adjuvanted Pandemic Influenza A Vaccines for Preventing Pandemic Influenza Acute Respiratory Illness Visits in 4 U.S. Communities

Abstract: We estimated the effectiveness of four monovalent pandemic influenza A (H1N1) vaccines (three unadjuvanted inactivated, one live attenuated) available in the U.S. during the pandemic. Patients with acute respiratory illness presenting to inpatient and outpatient facilities affiliated with four collaborating institutions were prospectively recruited, consented, and tested for influenza. Analyses were restricted to October 2009 through April 2010, when pandemic vaccine was available. Patients testing positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
79
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 23 publications
13
79
0
1
Order By: Relevance
“…Our point estimate of ca 75% VE for the 2013/14 nonadjuvanted TIV against influenza A(H1N1)pdm09 is comparable, if not exceeding, 2009 estimates for nonadjuvanted formulations of the monovalent pandemic vaccine used in the US (ca 60%) [26,27], albeit lower than the 93% VE estimated by our sentinel system for the 2009 AS03-adjuvanted pandemic vaccine used in Canada [10]. The 2013/14 mid-season VE estimate against influenza A(H1N1)pdm09 of ca 75% is in the upper range of recent seasons' VE estimates for nonadjuvanted TIV against A(H1N1)pdm09 reported since 2010 from Canada [11,12,21], Europe [28][29][30][31][32] and the US [33][34][35], which span ca 60-80%.…”
Section: Discussionsupporting
confidence: 54%
“…Our point estimate of ca 75% VE for the 2013/14 nonadjuvanted TIV against influenza A(H1N1)pdm09 is comparable, if not exceeding, 2009 estimates for nonadjuvanted formulations of the monovalent pandemic vaccine used in the US (ca 60%) [26,27], albeit lower than the 93% VE estimated by our sentinel system for the 2009 AS03-adjuvanted pandemic vaccine used in Canada [10]. The 2013/14 mid-season VE estimate against influenza A(H1N1)pdm09 of ca 75% is in the upper range of recent seasons' VE estimates for nonadjuvanted TIV against A(H1N1)pdm09 reported since 2010 from Canada [11,12,21], Europe [28][29][30][31][32] and the US [33][34][35], which span ca 60-80%.…”
Section: Discussionsupporting
confidence: 54%
“…Surveillance data from Denmark and North Denmark Region report an uptake in risk groups of 50% and 48%, respectively, in 2010,5 and a recent Danish study found that only 10 of 53 patients admitted to ICUs in 2009–2010 had been vaccinated, mostly due to chronic co‐morbidities 1. The role of vaccination is unclear at the individual level, but effectiveness at the public health level varying from 49% to 93% is reported in recent studies from the US, Canada, and Australia11, 12, 13; hence, the importance is acknowledged by WHO.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic variables that could affect the distribution of influenza A infections in populations are gender [16][17][18][19], age [15], clinical signs [20], vaccination against flu [21], usage of antimicrobials [22,24], smoking habits [25,29], and ethnicity [30,31].…”
Section: Introductionmentioning
confidence: 99%